Improving unsegmented network coding for opportunistic routing in wireless mesh network - Chen Chen; Chao Dong; Fan Wu; Hai Wang; Laixian Peng; Jingnan Nie (2012 IEEE Wireless Communications and Networking Conference (WCNC), 2012)
Unsegmented network coding was incorporated into opportunistic routing to improve inefficient schedule of segmented network coding due to delayed feedback. However, most unsegmented network coding schemes fail to constrain the size of decoding window. Large decoding window not only challenges limited computational ability and decoding memory in practical environments, but also introduces large decoding delay, which is undesirable in delay sensitive applications. In this paper, we prove that the possibility of unacceptably large decoding window is innegligible, and verify the necessity of handling decoding window. To solve the issue, we argue that the number of unknown packets injected into the network must be strictly constrained at the source. Based on the idea, we improve unsegmented network coding scheme for opportunistic routing. Simulation results shows that the solution is robust to losses. In addition, to achieve optimal throughput, the redundancy factor should be selected larger than the reciprocal of end-to-end delivery ratio.